2023
DOI: 10.3389/fcell.2023.1150273
|View full text |Cite
|
Sign up to set email alerts
|

Gap junction Delta-2b (gjd2b/Cx35.1) depletion causes hyperopia and visual-motor deficiencies in the zebrafish

Abstract: The zebrafish is a powerful model to investigate the developmental roles of electrical synapses because many signaling pathways that regulate the development of the nervous system are highly conserved from fish to humans. Here, we provide evidence linking the mammalian connexin-36 (Cx36) ortholog gjd2b/Cx35.1, a major component of electrical synapses in the zebrafish, with a refractive error in the context of morphological, molecular, and behavioral changes of zebrafish larvae. Two abnormalities were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…OCT has also been used to study the structural changes that occur in the eye as a result of refractive errors. [1] In this study, we used a custom-developed 1310 nm OCT to study the structural changes in the eyes of zebrafish with genetically modified genes. We found that zebrafish with a loss of gjd2b/Cx35.1, a zebrafish ortholog of the human CX36/GJD2, exhibited hyperopia.…”
Section: Introductionmentioning
confidence: 99%
“…OCT has also been used to study the structural changes that occur in the eye as a result of refractive errors. [1] In this study, we used a custom-developed 1310 nm OCT to study the structural changes in the eyes of zebrafish with genetically modified genes. We found that zebrafish with a loss of gjd2b/Cx35.1, a zebrafish ortholog of the human CX36/GJD2, exhibited hyperopia.…”
Section: Introductionmentioning
confidence: 99%